Pre-applied mechanically bonded waterproofing membranes: Bond strength of nonwovens to concrete and influencing parameters. (1st June 2023) - Heinlein, Ulli; Freimann, Thomas
Abstract: Pre-applied bonded membranes are used for waterproofing on the outside of concrete basements and are installed prior to the reinforcement, e.g., on a formwork. They often use nonwovens as a bonding layer and must ensure a sufficient bond both during stripping and use. However, it is not yet known how the bond develops and how it depends on concrete placement conditions. Hence, this study tested ten nonwovens for their bond to concrete in pull-off tests according to DIN EN 1542, varying the fresh concrete and concrete placement. The bond strength for all nonwovens developed proportionally to the concrete tensile splitting strength at a factor of 18–56% and was, e.g., 0.40–0.78 MPa after two days. The development was approximated by a fib model code approach, with higher concrete tensile splitting strengths and lighter nonwovens resulting in better bond strengths. In comparison with the reference tests, the bond strength was reduced for larger distances to the internal vibrator (max. −35%), higher w/c ratios of the fresh concrete, and nonwovens with higher basis weights. Also, water movements and air voids deviated the bond strength of vertically oriented nonwovens by −25% to +35% compared to reference values. Video recordings and measurements of the w/s ratio in the nonwoven complemented the results and showed that the nonwovens behave similarly to Controlled Permeable Formworks and separate excess water from the fresh concrete. As a result, the w/c ratio of the cement paste in the bonding zone changes, affecting the bond strength. Highlights: Ten nonwovens were used to investigate the bond strength to concrete in pull-off tests. The bond strength is proportional to the tensile splitting strength of concrete. The cement matrix strength in the bonding zone influences the bond strength. Lighter nonwovens have higher bond strengths as they retain less excess water from the fresh concrete.